Multiculturalismo e direitos dos ??ndios: o caso do povo Kaingang do oeste de Santa Catarina - Prola J??nior, Carlos Humberto (2016)
This study aims at demonstrating that the history of indigenous peoples in our country is set by genocide, slavery, expulsions and forced assimilation. From evolutionary ideas, the Brazilian state bet that the indians would always disappear. However, anthropological theories more appropriate to empirical realities ??? that permeate the new paradigm established by the Constitution of 1988, which devotes a multiethnic state and the right to social differentiation???, demonstrate that the ideas of acculturation, supremacy among human societies and that the isolation would be essential to the preservation of ethnic identity are inappropriate. In Santa Catarina, with the consolidation of the West area from the state, a new movement of colonization of the region begins, aggravating the raids on Kaingang people???s territory. However, in the late 1970???s, showing their status as protagonists of their own history, the Kaingang people promoted a revival movement from their traditional lands, starting to articulate their rights claims towards the state agencies. This study establishes a theoretical framework for a proper consideration of these issues, trying to avoid the extremes of cultural relativism, on one hand, and the homogenizing universalities on the other. The analysis indicates that state neutrality in relation to any conception of good life advocated by liberalism ??? from an atomistic conception of the human being, artificial and disconnected from reality, ignoring the membership ties to the community, as shown by the communitarian critique ??? has been synonymous with invisibility and death for indigenous peoples. Thus, the study focuses on the demands for recognition policies, which requires that public institutions no longer ignore it, but admit the cultural specificities, implementing politics of difference that recognizes the unique identity of each individual or group. In addition, this study also analyzes the multicultural liberalism that advocates the need to supplement liberalism and its universal human rights, attributing to ethnocultural minorities a specific set of rights. From this theoretical framework, several concrete situations related to the Kaingang People from the West of Santa Catarina are discussed, such as ranging from the right to self-determination, autonomy and self-government; exercise of specifically indigenous jurisdiction and enforcement of traditional punishments; inaccuracies and misunderstandings that permeate the operation of criminal justice in our country in cases involving indigenous rights; pressure faced by Kaingang in relation to permanent possession of their territories; issues involving indigenous education and the challenge of preserving their mother tongue.